Smart technologies and the future of concussion prevention in ice hockey - Gråstén, Arto (Frontiers in Sports and Active Living, 2025)
BackgroundConcussions in ice hockey remain a major concern, especially among young players. Current helmets mainly protect against skull fractures but offer limited shielding from brain acceleration forces.MethodsA narrative review of epidemiological studies, helmet safety research, and technological innovations in other sports like cycling, equestrian, and football was conducted to assess limitations of current helmets and the potential for advanced protective systems.ResultsConcussion rates remain relatively high, with inconsistent diagnoses making comparisons difficult. Standard helmets show minimal performance differences and have limited ability to reduce rotational forces. Innovations like wearable sensors integrated into helmets offer notable protection benefits in other sports. However, hockey-specific concerns include repeated impacts, usability, and weight limits.DiscussionSmart technologies such as airbag helmets present a viable path toward enhanced protection in ice hockey. Translating these solutions requires engineering adaptation, interdisciplinary collaboration, and cultural acceptance, especially urgent in youth sport, where long-term risks are greatest.